Platelet to Lymphocyte Ratio (PLR) Value in Normotency, Preeclampsia and Severe Preeclampsia - Rony Falty Sibagariang; Bambang Wibowo (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : Hyperactivation of the inflammatory response in preeclampsia causes a significant increase in the number of leukocytes. Platelet to Lymphocyte Ratio (PLR) has been known as a marker of systemic inflammatory response. In preeclampsia, the role of PLR markers is still uncertain regarding the ability of clinical evaluation, differential diagnosis and evaluation of patient prognosis. AIMS :  To analyze differences in platelet to lymphocyte ratio (PLR) values in normotensive, preeclampsia, and severe preeclampsia pregnancies METHOD : Analytical observational study with cross sectional design with 90 samples consisting of 30 normotensive pregnancies, 30 preeclampsia and 30 severe preeclampsia. Evaluation is carried out on the platelet to lymphocyte ratio (PLR) value. Analysis was carried out using the SPSS 32 edition application. Results are significant if p<0.05. RESULT :  Comparison between the normotensive group versus preeclampsia versus severe preeclampsia showed that platelet levels decreased but not significantly (p=0.081), lymphocyte levels increased significantly (p<0.001) and PLR values decreased significantly (p<0.001) as the degree of severity increased preeclampsia. In the severe preeclampsia group, the lowest platelet levels, the highest lymphocyte levels and the lowest PLR values were obtained. Patients with a PLR value < 104.62 have an 8.43x (OR 8.43; CI95% 3.12-22.78) higher risk of experiencing severe preeclampsia compared to subjects with a PLR value > 104.62. CONCLUSION : The PLR value was significantly lowest in the severe preeclampsia group.